PENGARUH TEHNIK HYPNOBIRTHING TERHADAP PEMBUKAAN SERVIKS DAN PENURUNAN KEPALA PERSALINAN NORMAL PADA IBU PRIMIGRAVIDA KALA I - Muhidayati, Wiwik; Luluk, Sri (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
ABSTRAK Background: The old Partus may jeopardize the safety of the mother and fetus, so it is important to pursue the progress of labor, especially for primigravida mothers. Hypnobirthing technique is one effortto help the progress of laborMethods: This study was a quasi experiment post test only with control group. The population of this research is all mothers of maternal first in BPM Lamongan City Area. The sample was taken by accidental sampling technique and the sample size was 32 respondents, divided into experimental group and control group. The progress of labor was measured by four indicators recorded in partograf. namely: his frequency, duration of his, cervical opening and decreased head.gResults: In the control group, the advancement of cervical opening of the first 4 hours averaged 2.12 cm and most did not progress head-drop. in the experimental group, the advancement of cervical opening of the first 4 hours averaged 3.56 cm and most of them progressedmb head-drop. The result of independent T-test showed cervical opening 0,007; and p-value head decrease of0.000.Conclusion.There is an influence of hypnobirthing technique on the progress of labor in the mother of primigravida when I normal. Keywords: Hypnobirthing, cervical opening and head drop, Primigravida